Análisis económico, técnico y ambiental de la implementación del generador eléctrico de la Universidad Técnica de Cotopaxi extensión La Maná - Paredes Lidioma, Luis Anibal (2014)
The study of this research determines the feasibility of installing a generator of electricity in Block A, from an economic, technical, and environmental point of view. The thesis involves the study of the demand for the service (generator of electricity). It is analyzed from the service definition through the analysis of demand. At the end of the stage, it will have a clear view of current conditions of energy demand of Block A which allows deciding how convenient the installation of a generator from the point of view of its potential demand is.